THE APPLICATION OF WEB BASED LEARNING BY USING A BLENDED LEARNING APPROACH IN SPEAKING II CLASS OF ENGLISH EDUCATION STUDY PROGRAM OF TEACHER TRAINING AND EDUCATION FACULTY OF BANDAR LAMPUNG UNIVERSITY - Thea Marisca Marbun B.N; Arnes Yuli Vandika (International Conference on Education and Language (ICEL), 2016)
This paper aims to investigate the application by using modern technology of Schoology in teaching English as a second language. It discusses Blended Learning approach which can assist English language students to improve their learning skills by using technology. The study was conducted with the second semester students of English Study Program in Bandar Lampung University. The instrument was the questionnaire designed to identify students’ views on blended learning. Results revealed the students’ views on blended learning process, such as ease of use of the web environment, evaluation, and face to face environment.